Pengaruh Lingkungan Fisik Sekolah dan Motivasi Belajar Terhadap Hasil Belajar Siswa - Jihan Irbah; Armida Armida (Jurnal Salingka Nagari, 2024)
The research purpose is to reveal 1) the school's physical environment impact on the motivation for learning of class XI IIS students at SMA Pertiwi 1 Padang, 2) the school's physical environment impact on the outcomes of learning of class XI IIS SMA Pertiwi 1 Padang, 4) the school's physical environment impact on student outcomes of learning with student motivation for learning as mediation. This research is descriptive and quantitative. The population for this research was all class XI IIS SMA Pertiwi 1 Padang, with 100 people. The sampling method used total sampling and a total of 100 respondents was obtained. The technique for analysis in this research uses the path analysis method using SPSS version 25. The research results show that: 1) the physical environment of the school has a significant impact on the motivation for learning of class XI IIS students at SMA Pertiwi 1 Padang, 2) the physical environment of the school has a good and significant impact on the outcomes of learning in class XI IIS students at Pertiwi 1 Padang High School, 3) learning motivation has a good and significantly impact on the outcomes of learning in class IIS SMA PERTIWI 1 Padang. Based on the research done, it was found that the school's physical environment and motivation for learning influenced the outcomes of learning in class XI IIS students at Pertiwi 1 Padang High School by 70.8%.